How to print fabric kitchen-table techniques for over 20 hand-printed home accessories - Shah, Zeena (D&C, 2015)
"In this beautiful yet practical project book, Zeena shows you how to create contemporary textiles though 20 easy-to-master techniques, each accompanied by a simple sewing project to put your prints on display straight away"--Provided by Amazon.